2007
DOI: 10.1103/physrevd.75.023507
|View full text |Cite
|
Sign up to set email alerts
|

Uncorrelated universe: Statistical anisotropy and the vanishing angular correlation function in WMAP years 1–3

Abstract: The large-angle (low-ℓ) correlations of the Cosmic Microwave Background (CMB) as reported by the Wilkinson Microwave Anisotropy Probe (WMAP) after their first year of observations exhibited statistically significant anomalies compared to the predictions of the standard inflationary big-bang model. We suggested then that these implied the presence of a solar system foreground, a systematic correlated with solar system geometry, or both. We re-examine these anomalies for the data from the first three years of WM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
564
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 368 publications
(590 citation statements)
references
References 67 publications
26
564
0
Order By: Relevance
“…Furthermore, the other CMB anomalies associated with large-angle correlations (Land & Magueijo 2005;Copi et al 2006Copi et al , 2013 should be revisited in light of these findings.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Furthermore, the other CMB anomalies associated with large-angle correlations (Land & Magueijo 2005;Copi et al 2006Copi et al , 2013 should be revisited in light of these findings.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…inv ( ,i) . Copi et al (2006) found thatn 2 ·n 3 = 0.962 for the TOH map. The corresponding values obtained from the analysis of the WMAP 7-year data is 0.937.…”
Section: Low Power On Large Angular Scalesmentioning
confidence: 99%
“…In the subsequent sections, to be conservative, we use S (3,3) = 0.798 (Copi et al 2007), obtained using the cleaned full sky map of Tegmark, de Oliveira-Costa, & Hamilton (2003) (TOH; henceforth). An alternative statistic that tests the planarity is given by the angular momentum dispersion (de Oliveira-Costa et al (2004)).…”
Section: Low Power On Large Angular Scalesmentioning
confidence: 99%
See 2 more Smart Citations